2019
DOI: 10.21272/sec.3(3).98-107.2019
|View full text |Cite
|
Sign up to set email alerts
|

Influential Factors of Green Consciousness in Bangladesh: A Pragmatic Study on General Public in Dhaka City

Abstract: Green is the buzz term in the globe. Green is a crucial term that can mean a wide diversity of things to different people. Ecological approach is a current information that can be applied to everywhere. Bangladeshi general public must adopt ecologically sound behavior to keep up the clean environment. By location, Bangladesh falls in the coastal region. Bangladesh is going to be worst sufferers due to the effect of quick climate change throughout the globe. Bangladesh is an emerging and densely populated count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Most of the farmers have insufficient cash reserves to purchase 2WT along with a CA planter (VMP) for minimum tillage. They have to depend mainly on the local service providers of CA (Bell et al, 2019) and other machineries for tillage and threshing operations (Alam, 2019). About 55% of farmers identified the inability to purchase a CA planter as a future challenge for CA adoption.…”
Section: Challenges For Ca Adoptionmentioning
confidence: 99%
“…Most of the farmers have insufficient cash reserves to purchase 2WT along with a CA planter (VMP) for minimum tillage. They have to depend mainly on the local service providers of CA (Bell et al, 2019) and other machineries for tillage and threshing operations (Alam, 2019). About 55% of farmers identified the inability to purchase a CA planter as a future challenge for CA adoption.…”
Section: Challenges For Ca Adoptionmentioning
confidence: 99%
“…Some researchers have devoted their work to the study of energy independence of all types of resources and investments in renewable energy as a guarantee of sustainable development [9][10][11][12][13][14][15][16][17]. The study of forecasting of the country's development strategy based on social progress and macroeconomic stability, lifelong learning, as well as the country's food security and the role of sustainable development have been reflected in numerous scientific papers [18][19][20][21][22][23][24][25][26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The scientists in the papers [46][47][48][49][50] demonstrated that corporate social responsibility influences the brand. The group of the scientists proved that an imbalance in financial sectors [51][52][53][54][55][56], green development [57][58][59][60][61][62][63][64][65][66][67], shadow economy and corruption [68][69][70][71][72][73][74][75], innovation technologies [67,[76][77][78][79][80][81][82][83] and a country's attractiveness [67,[82][83][84][85] influence the investment climate in the country and the company's image [86][87][88][89][90]…”
mentioning
confidence: 99%